Mitochondrial Respiration of Platelets: Comparison of Isolation Methods - Vernerova, Andrea; Garcia-Souza, Luiz Felipe; Soucek, Ondrej; Kostal, Milan; Rehacek, Vit; Kujovska Krcmova, Lenka; Gnaiger, Erich; Sobotka, Ondrej (Biomedicines, 2021)
Multiple non-aggregatory functions of human platelets (PLT) are widely acknowledged, yet their functional examination is limited mainly due to a lack of standardized isolation and analytic methods. Platelet apheresis (PA) is an established clinical method for PLT isolation aiming at the treatment of bleeding diathesis in severe thrombocytopenia. On the other hand, density gradient centrifugation (DC) is an isolation method applied in research for the analysis of the mitochondrial metabolic profile of oxidative phosphorylation (OXPHOS) in PLT obtained from small samples of human blood. We studied PLT obtained from 29 healthy donors by high-resolution respirometry for comparison of PA and DC isolates. ROUTINE respiration and electron transfer capacity of living PLT isolated by PA were significantly higher than in the DC group, whereas plasma membrane permeabilization resulted in a 57% decrease of succinate oxidation in PA compared to DC. These differences were eliminated after washing the PA platelets with phosphate buffer containing 10 mmol·L-1 ethylene glycol-bis (2-aminoethyl ether)-N,N,N',N'-tetra-acetic acid, suggesting that several components, particularly Ca2+ and fuel substrates, were carried over into the respiratory assay from the serum in PA. A simple washing step was sufficient to enable functional mitochondrial analysis in subsamples obtained from PA. The combination of the standard clinical PA isolation procedure with PLT quality control and routine mitochondrial OXPHOS diagnostics meets an acute clinical demand in biomedical research of patients suffering from thrombocytopenia and metabolic diseases.
Keywords: flow cytometry; platelet apheresis; mitochondria; human platelets; high-resolution respirometry; density gradient centrifugation; thrombocytes; oxidative phosphorylation